Pendampingan Budidaya Ayam Bertelur oleh Mahasiswi Kkn Unzah Dengan Pemilik Umkm Desa Nogosaren - Indar Parawangsa, Hofifah; Sholehah, Riskawati (Kalam Nusantara Institute, 2026)
The activity of the Real Work Lecture program is a field activity for students who are taking the final part of undergraduate education which aims to increase student empathy regarding conditions in society through the implementation of multidisciplinary science, and as a form of increasing student communication with the community. Implementation of the ZAinul Hasan University real-life lecture program which takes place in Nogosaren Village, Gading District, Probolinggo Regency. Egg-laying chicken cultivation is one of the businesses that is in great demand nowadays, the demand for chickens is high on the market. Egg-laying chickens that are easy to develop are one of the supporting factors for the progress of egg-laying chickens, and a good level of egg resistance to weather changes supports fast development and makes it easy for farmers to make egg-laying chickens the right choice for business.